Conflict in Myanmar war, politics, religion - Cheesman, Nick; Farrelly, Nicholas 1982- (Myanmar update series, 2016)
Showcases innovative research by a rising generation of scholars, analysts and practitioners about the past five years of political transformation in Myanmar. Each of its seventeen chapters builds on theoretically informed, evidence-based research to grapple with significant questions about ongoing violence and political contention.